2019
DOI: 10.1002/mnfr.201900183
|View full text |Cite
|
Sign up to set email alerts
|

Targeting PLIN2/PLIN5‐PPARγ: Sulforaphane Disturbs the Maturation of Lipid Droplets

Abstract: Scope The effects of sulforaphane (SFN) on the maturation of lipid droplets (LDs)—the storage units for free fatty acids and sterols as triacylglycerides (TAG) and cholesterol esters (CE)—are far from being understood, despite the fact that SFN is known to be beneficial for ameliorating lipid metabolism disorders. Methods and Results High‐fat‐intake models are established in both HHL‐5 hepatocytes and rodents. The numbers and sizes of LDs are decreased by SFN. The accumulation of lipid core components (TAG & C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…[ 57,58 ] Notably, some genes, such as Ubc and Plin2 , were involved in lipid oxidation and cell proliferation. [ 59,60 ] In addition, transcriptional alteration of some genes indicated that TDT could potentially induce immune responses in vivo. For example, CSF3 , a cytokine regulating the development and function of granulocytes and macrophages, was upregulated upon the drug treatment.…”
Section: Resultsmentioning
confidence: 99%
“…[ 57,58 ] Notably, some genes, such as Ubc and Plin2 , were involved in lipid oxidation and cell proliferation. [ 59,60 ] In addition, transcriptional alteration of some genes indicated that TDT could potentially induce immune responses in vivo. For example, CSF3 , a cytokine regulating the development and function of granulocytes and macrophages, was upregulated upon the drug treatment.…”
Section: Resultsmentioning
confidence: 99%
“…It is shown in our data that leptin treatment has increased the mRNA and protein expression of PPARγ, HSL, ATGL, and LPL. Other reports have found that PPARγ induces the accumulation of Plin5 [ 32 ], and further HSL and ATGL can interact with Plin5 to regulate lipolysis [ 22 , 33 ]. Interestingly, we found through preliminary experiments that the JAK2/STAT3 signaling pathway inhibitor (SD1008) and leptin co-treatment of 3T3-L1 did not cause changes in the expression of Plin5 mRNA, but the protein level of Plin5 was still significantly up-regulated.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Recently it has been shown that perilipins are regulated by peroxisome proliferator-activated receptor gamma (PPAR-gamma) which, when inhibited results in the down-regulation of PLIN2 , affecting LSD formation. 59 RORA encodes nuclear receptor ROR-alpha, which is a regulator of lipid homeostasis through PPAR-gamma. 60 Hence, using TWAS, we have connected two genes involved in lipid metabolism through PPAR-gamma.…”
Section: Discussionmentioning
confidence: 99%